Pelanggaran Lalu Lintas di Wilayah Hukum Polres Gorontalo Tahun 2022– 2024 - Muhamad Zulkifli Lamatenggo; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
A traffic violation is a violation or action that is contrary to traffic laws or regulations, in accordance with Law Number 22 of 2009 which was passed by the DPR-RI on 22 June 2009. The aim of this research is to get a picture of traffic violations in the Gorontalo Police area.  The research method used is qualitative analysis with a literature study approach through collecting primary and secondary data on reports on the number of traffic violations in the Gorontalo Police area from 2022 to 2024. From the research results it was found that during the last 3 years from 2022 to 2024 there were past violations traffic violations in the Gorontalo Police area that are most frequently reported are traffic violations regarding vehicle equipment, documents and driver equipment with more efforts being made in the form of persuasive efforts in the form of giving warning sanctions in take action against traffic violations rather than imposing fines according to the articles violated. There is also a downward trend in the number of violations reported in the Gorontalo Police area from 2022 to 2024.